Increases in Stressors Prior to-Versus During the COVID-19 Pandemic in the United States Are Associated With Depression Among Middle-Aged Mothers - Taylor, Brittany K.; Frenzel, Michaela R.; Johnson, Hallie J.; Willett, Madelyn P.; White, Stuart F.; Badura-Brack, Amy S.; Wilson, Tony W. (Frontiers in Psychology, 2021)
Working parents in are struggling to balance the demands of their occupation with those of childcare and homeschooling during the COVID-19 pandemic. Moreover, studies show that women are shouldering more of the burden and reporting greater levels of psychological distress, anxiety, and depression relative to men. However, research has yet to show that increases in psychological symptoms are linked to changes in stress during the pandemic. Herein, we conduct a small-N study to explore the associations between stress and psychological symptoms during the pandemic among mothers using structural equation modeling, namely latent change score models. Thirty-three mothers completed questionnaires reporting current anxious and depressive symptoms (Beck Anxiety and Depression Index, respectively), as well as stressful life experiences prior to- versus during the pandemic (Social Readjustment Rating Scale). Women endorsed significantly more stressful events during the pandemic, relative to the pre-pandemic period. Additionally, 58% of mothers scored as moderate-to-high risk for developing a stress-related physical illness in the near future because of their pandemic-level stress. Depressive symptoms were associated with the degree of change in life stress, whereas anxiety symptoms were more related to pre-pandemic levels of stress. The present study preliminarily sheds light on the nuanced antecedents to mothers’ experiences of anxious and depressive symptoms during the COVID-19 pandemic. Although further work is needed in larger, more diverse samples of mothers, this study highlights the potential need for appropriate policies, and prevention and intervention programs to ameliorate the effects of pandemics on mothers’ mental health.